Roles of Mesenchymal Stem Cells in Spinal Cord Injury - Jing Qu; Huanxiang Zhang (Stem Cells International)
Spinal cord injury (SCI) represents one of the most complicated and heterogeneous pathological processes of central nervous system (CNS) impairments, which is still beyond functional regeneration. Transplantation of mesenchymal stem cells (MSCs) has been shown to promote the repair of the injured spinal cord tissues in animal models, and therefore, there is much interest in the clinical use of these cells. However, many questions which are essential to improve the therapy effects remain unanswered. For instance, the functional roles and related molecular regulatory mechanisms of MSCs in vivo are not yet completely determined. It is important for transplanted cells to migrate into the injured tissue, to survive and undergo neural differentiation, or to play neural protection roles by various mechanisms after SCI. In this review, we will focus on some of the recent knowledge about the biological behavior and function of MSCs in SCI. Meanwhile, we highlight the function of biomaterials to direct the behavior of MSCs based on our series of work on silk fibroin biomaterials and attempt to emphasize combinational strategies such as tissue engineering for functional improvement of SCI.